Binapthyl Schiff base diamine complex covalently bonded to modified SBA-15: synthesis, characterization and catalytic application - Sharma, Priti; Singh, A. P. (Catalysis Today, 2012)
Protected mesoporous SBA-15 phase was synthesized by grafting the complex Chloro (S,S)(-)[N-3-tert-butyl-5-chloromethyl salicylidene]-N'-[3',5'-di tert-butyl salicylidene] 1,1'-binapthyl-2,2'-diamine manganese(III) through the reactive 3-aminopropyl trimethoxysilane(3-APTMS) group. The surface properties of the functionalized catalyst were analyzed by a series of characterization techniques like elemental analysis, XRD, N-2 sorption measurement isotherm, FT-IR, XPS, and solid state C-13 NMR. The screening of the catalyst Mn(III)-L-SBA-15 and neat Mn(III)-L complexes was done for the oxidation reaction of thioanisole (methyl phenyl sulfide) using TBHP as an oxidant. Mn(III)-L-SBA-15 catalyst shows higher activities and exhibit enantiomeric excess comparable to homogeneous catalyst. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: -OH protected NH2-SBA-15; Binaphthyl Schiff base ligand; Ordered mesoporous materials; Sulfoxidation; Thioanisole

Chiral (VO)-O-IV-Sal-Indanol complex over modified SBA-15: an efficient, reusable enantioselective catalyst for asymmetric sulfoxidation reaction - Lazar, Anish; Sharma, Priti; Singh, A. P. (Microporous and Mesoporous Materials, 2013)
A reusable, mesoporous, heterogeneous vanadium complex, (VO)-O-IV-Sal-Ind-SBA-15 has been synthesized first time from (1R,2S)-(+)-Cis-1-amino-2-indanol for enantioselective sulfoxidation reaction. The physico-chemical properties of the functionalized catalyst were analyzed by a series of characterization techniques like XRD, N-2 sorption measurement isotherm, TEM, FT-IR, XPS, EPR, DRS UV-Visible, ICP-OES and solid & liquid state C-13, Si-29 and V-51 NMR spectroscopy. Powder X-ray diffraction patterns, TEM and N-2 physisorption analysis confirmed the retention of mesoporous structure after various modifications. Solid-state NMR (C-13 CP-MAS NMR, Si-29 MAS NMR) and FT-IR analysis certified the integrity of organo-catalyst residing inside the pore channels of the mesoporous support. Further, XPS, EPR, V-51 NMR and DRS UV-Visible analyses help to find out the oxidation state and coordination environment of vanadium in (VO)-O-IV-Sal-Ind-SBA-15. Catalytic evaluation in asymmetric sulfoxidation reaction of sulfides indicated that VOIV-Sal-Ind-SBA-15 exhibited higher catalytic activity, stability, reusability and comparable enantioselectivity than SBA-15, PrNH2-SBA-15, neat (VO)-O-IV-Sal-Indanol complex and without catalyst. The effect of different catalysts, temperature, solvents and substrates on sulfoxidation reaction were examined in order to optimize the conversion and enantioselectivity of thioanisoles to sulfoxides. Crown Copyright (C) 2012 Published by Elsevier Inc. All rights reserved.
Keywords: (1R; 2S)-(+)-Cis-1-amino-2-indanol; Asymmetric sulfoxidation; Heterogeneous vanadium complex; Mesoporous; Thioanisole